Navigating CD-Roms: An Exploration of Children Reading Interactive Narratives. - James, Rebecca (Children's Literature in Education)
Explores the impact of non-fiction electronic texts on the interactive response of children. Description of the interaction with the visual text of the legend of "Payuta"; Manipulation of the visual point of view and the reader's emotional involvement with the story; Suspense in verbal and visual text.